Thiazide Diuretics and Their Importance in Cardiac Diseases (Eurasian Medical Research Periodical, 2025)
Thiazide diuretics are widely used agents in the managing cardiovascular diseases, especially hypertension and chronic heart failure. They act by inhibiting sodium-chloride symporters in the distal convoluted tubule, leading to effective blood pressure reduction. This article explores their mechanism of action, clinical applications, and comparative benefits. A separate section highlights the etiology and classification of heart failure to provide clinical context. The pharmacodynamics and pharmacokinetics of individual thiazides—hydrochlorothiazide, chlorthalidone, indapamide, and metolazone—are discussed in detail. Evidence-based protocols and case studies further demonstrate their clinical value.